The study of the effects of government issued cooling measures on privately owned properties in Singapore - Vanmathi, Muthiah (2019)
The Residential Property Market in Singapore has been growing rapidly over the years. The private sector, in particular, has seen a drastic increase in property prices. The Singapore government had to step in, with various cooling measures implemented over the years, to deflate the property market. The inflation of the market, if left unchecked, may lead to other unintended financial and economic issues in the future. This report aims to analyse past resale transactions of private residential properties with Condominiums in particular and identify the areas in which the effects of cooling measures are lesser. This will give investors a clearer picture on which areas they can possibly invest in. This investigation compared the effects of cooling measures on unit prices with respect to the various geographical regions (districts) in Singapore, the floor numbers of condominiums and the age of a condominium. It is noted that there are general trends among these comparisons that are affected by individual preferences such as the preference for higher floors and younger condominiums. The deflating effects of cooling measures can be observed when comparing unit prices of condominiums with respect to floor numbers of units and age of the condominium. While its effect is seen in all districts, the exact degree of its effect is inconclusive as there are many other factors involved. On the other hand, the Central district seems to exhibit the least effect from CMs as its prices depend heavily on global events. Hence, as an investor, it would be lucrative to invest in the Central district as it would yield the most profit, but it requires high capital comes with a risk of its volatility to global events. One would need to be updated with global news and events to mitigate the risks. If one were to invest in any of the other districts, higher floor units will require a high initial investment but will fetch a high profit margin as well. Additionally, a younger condominium would be the safest option as purchasing an older condominium with the intent to en-block it down the road will be extremely risky.